THE INFLUENCE OF ECONOMIC DEVELOPMENT AND SOCIAL STABILITY ON ENTERPRISE MANAGEMENT - Тетяна Харченко; Мінь Чжао (Економіка та суспільство, 2023)
Under the background of globalization and information technology, the competitiveness of enterprises has become an important symbol of a country or even a region. The formation of enterprise competitiveness is closely related to many factors, among which economic development and social stability play a positive role that cannot be ignored in the long-term and stable development of enterprises. Economic development and social stability have laid a solid foundation for the development of enterprises, enabling them to form a relationship of complementary advantages, mutual benefit and value sharing among the government, market and society. However, enterprise management as an enterprise under the background of economy and socialization through the labor and labor resources coordination and distribution, help enterprises to control cost, efficient configuration, promote production plays a key role, therefore, enterprise management is one of the important elements affecting the enterprise core competitiveness, in turn, reflects the present situation of contemporary economic and social development. The effective development of enterprises not only plays a helping role in helping the whole national economy, but also plays an important role in solving the employment problem of social workers, creating wealth, eliminating poverty, reducing the gap between the rich and the poor, promoting consumption and stabilizing the society. Therefore, to explore the impact of economic development and social stability on enterprise management is to study the impact of economic development and social stability on the sustainable development and improve the comprehensive competitiveness of enterprises, starting from the core meaning of enterprise development.